Vloga matičnih celic pri nastanku raka mlečne žleze - Keber, Rok (Acta agriculturae Slovenica, 2010)
Breast cancer is the most common type of cancer in women worldwide but also very common in domestic cats and dogs. Recent research in mammary gland biology has provided support for the cancer stem cell-hypothesis. The main focus of this hypothesis is that tumor originates from mammary stem or progenitor cells as a result of deregulation of the normally precise regulated process of self-renewal, which is their main characteristics. As a result, tumors contain and are driven by a cellular subcomponent that retains key stem-cell properties and enable development and differentiation of the tumor tissue, which results in extensive cellular heterogeneity. The role of cancer stem cells in cancer tissues resembles the role of normal stem cells in healthy tissue. Cancer stem cells have been first discovered in hematopoietic and later in solid cancers like brain, prostate, colon, pancreas and breast cancer. Identification of these cells in healthy and tumor breast tissue has helped to elucidate the origin of molecular complexity of breast cancer in humans and animals. The cancer stem-cell hypothesis has important implications for early detection and prevention of hereditary and sporadic form of breast cancer in humans. Aberrant stem cells with deregulated self-renewal mechanism are highly resistant to radiation and chemotherapy and therefore represent a central target in development of more effective drugs and therapies for breast cancer treatment.
Keywords: mlečne žleze; matične celice; rak (medicina)